INTERACTIVE USER FRIENDLY SOFTWARE TO MODEL THE PRICE OF HIGH ENERGY SAVING LAMPS COMPARED TO INCANDESCENT LAMPS - Mohd Arif, Nawar (Universiti Teknologi PETRONAS, 2007)
The objective of this Final Year Project is to develop a probability and statistics software for an engineering application to model the price of lamps to its many desirable characteristics and then suggesting the most suitable lamp to be used. Users use this software-modeling tool to estimate the price of lamp and to forecast the billing cost for a specific lamp by using the power consumption and time ofusage. The proposed framework of the system consists of three inter related components; the database will provide input to the model, the modeling and user interface that provides a channel for the user to communicate with the system. Three stages have been identified in order to develop the system. They are variable identification, statistical model development and the development of the software. Severalvariables have been identified but it is observed that the main variables that is quantifiable and to have effect on price are wattage (W), brightness (lumens), diameter (mm), length (mm), average lifetime (hour) and Correlated Color Temperature CCT (K). The model that was identified is multiple regression analysis. This model is then incorporated in an interactive interface.